Aproximar-se para dialogar: imigrantes venezuelanos e saúde mental - (:unkn) unknown (Universidade Federal do Amazonas, 2019)
The subject of migration is something that has been widely observed and discussed in our contemporary society, and the reason for studying this issue is related to the significant presence of Venezuelan immigrants in Manaus and the possibility of approaching these people to build dialogues about migration and mental health. In this sense, the objective of this study is to investigate from everyday life of a group of Venezuelans who are in the city of Manaus, in what way the migratory process is reflected on the mental health of this group. The research seek to describe the daily life of these people after migration, and through this describe what was realized in relation to difficulties and demands, to analyze how these issues are reflected on the mental health of this population, considering that, in this research, mental health is beyond psychopathology. It also discusses the conceptual aspects of migration and its derivatives, as well as on Macrocultural Psychology - PMC. This is a qualitative research with a descriptive approach. Participants were chosen by means of the technique Snowball in the Casa do Migrante João Batista Scalabrini, being monitored inside and outside the institution. Ethnography was also used to allow the insertion of the researcher in the daily life of the participants. The information was recorded in a field diary and served as an aid to the ethnographic description of their daily life. The topics of analysis were the discursive practices of the participants, in which the following categories are discussed: displacement motivations, rights, language, work and identity, longing, suffering and social support, being mental health a transversal category. Finally, the research results pointed out that the difficulties arising from the migration process act both negatively and positively under the mental health of the participants. It is noteworthy that the mental health we talk about in this research is seen and comprehended from a broader perspective, especially because it encompasses all aspects of life. It is hoped that the results of this research can contribute to the elaboration of public policies addressed to this population, as well as the accomplishment of other researches involving this theme.
Keywords: Imigrantes - Refugiados - Manaus (AM); Venezuelanos - Refugiados - Manaus (AM); Saúde mental - Refugiados - Manaus (AM); Ciências Humanas: Psicologia: Psicologia Social; Imigrantes venezuelanos; Saúde mental; Cotidiano; Diálogo